The national games experience in Taiwan: a retrospective review of mass-gathering sports events from 2017 to 2021 - Pei-Hsuan Ho; Ju-Chi Ou; Hon-Ping Ma; Chung–Shun Wong; Hua-Chen Lin; Chia-Hung Hsu (Scientific Reports)
Abstract Mass gatherings, particularly in the context of sporting events, pose distinct public health challenges, particularly regarding the medical needs of athletes. Despite the critical role of on-site medical care in reducing hospital transfers, studies that directly compare injury patterns across various sporting events are scarce. This study analyzed injury rates and severity among athletes participating in various sports during the National Games in Taiwan. By doing so, the study aimed to enhance medical preparedness for future large-scale sporting events. This retrospective study involved a chart review of athletes who sought medical support during the National Games in Taiwan in 2017, 2019, and 2021. Data on patient demographics, event type, injury characteristics, and the need for hospital transport were collected. Sports were categorized in accordance with the American Heart Association and American College of Cardiology classifications ( based on their static and dynamic components). Statistical analyses were conducted to determine injury rates and identify factors associated with hospital transfers. Over the three years, 20,585 athletes participated in the games, with 527 (2.56%) seeking medical support. Injury rates significantly varied among the groups of sports with differing static and dynamic demands. Sports classified as having both high static and dynamic demands had the highest injury rates. Handball, martial arts, and rowing resulted in the highest rates of medical support-seeking behavior. The need for hospital transport was more frequently associated with sports that involved both high static and dynamic demands. The study highlights the varying injury patterns across different sports in mass gatherings, with sports involving higher physical demands posing greater risks of injury. These findings underscore the importance of developing tailored medical preparedness strategies for different types of sports to ensure timely and effective provision of medical care during large-scale sporting events.